The Effect of Abuse History on Adolescent Patients with Feeding and Eating Disorders Treated through Psychodynamic Therapy: Comorbidities and Outcome - Strangio, Annamaria M.; Rinaldi, Lucio; Monniello, Gianluigi; Sisti, Leuconoe Grazia; de Waure, Chiara; Janiri, Luigi (Frontiers in Psychiatry, 2017)
Abstract Objectives: The first aim of our study was to compare the characteristics and co-morbidities of patients with eating disorders between those who suffered from a childhood abuse and those who did not. Our second aim was to analyze the differences in the outcome of the psychodynamic therapy between abused and not abused patients. Methods: 26 adolescent patients with eating disorders were assessed. Adolescent were evaluated by a single expert psychiatrist by checklists and questionnaires: EDI 3, SCL 90, BIS11, DES, GAF, SCID II and CTQ- SF. According to the results of CTQ- SF (cut- off ≥ 8), patients were divided into two groups: those who had experienced a history of abuse and those who had not. They underwent a psychodynamic psychotherapy and were assessed again after 12 months. Results: Eleven patients (42,3%) had a history of abuse according to CTQ score. No significant differences were found in abused and not abused patients in their demographic, clinical and comorbid characteristics (sex, age, type of eating disorder, comorbid impulse control, personality and addictive disorders). Abused patients showed a significantly higher score in many scale. The psychotherapeutic Intervention in patients with a history of abuse resulted only in a significant decrease in SCL - 90 Psychoticism dimension (p<0.05), whereas in patients with no history of abuse a significant decrease was found for SCL- 90 Somatization, Obsessive Compulsive and Phobic Anxiety dimensions , the SCL-90 Global Severity Index, the EDI-3 Interceptive Deficits and the Dissociative Experience Scale. Conclusion: Regarding the first aim of our study, we proved that history of abuse is not significantly related to patient comorbidities. Regarding our second aim, history of abuse was related to patient improvement only for psychotic symptoms; whereas patients who had not experienced an abuse improved in a variety of symptoms. Thus, abuse history can be considered as a negative prognostic factor for patients with eating disorders undergoing dynamic psychotherapy. However, this psychotherapy may have a role in preventing early psychotic disorders in patients with and without an history of abuse.